Service management training approach model as a step to increase the professionalism of employees in the security task force - Achmad Efendi (Trigin Publisher, 2023)
The Security Unit (Satpam) has the task of maintaining security and order in their work environment in a professional manner, so they are required to take part in education and training that supports their professionalism as security personnel who are able to provide satisfaction to the users of their services. This research aims to examine the influence of service training and relational management as professional standards for security guard work, as well as verifying the relationship between work professionalism and satisfaction with security guard service users. This mixed methods research took 40 security guards who attended service and relationship management training. Paired sample analysis obtained a value of 7.342 with a probability of 0.000 (p<0.05), proving that there was a significant increase in security guard competency after attending the training. The results of Pearson's analysis, obtained a coefficient value of 0.728 with a probability of 0.002 (p<0.05), which is proven to have a positive and significant relationship between the professionalism of security guards who have attended training and the satisfaction of service users. It can be concluded that service and relationship management training is able to increase professional competence and have an impact on service user satisfaction.